2022
DOI: 10.1001/jamanetworkopen.2022.8722
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perspectives of Overdiagnosis and Overtreatment of Low-Risk Papillary Thyroid Cancer in the US

Abstract: This survey study assesses physicians’ recommendations regarding overdiagnosis and overtreatment of thyroid nodules and low-risk papillary thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The notions of "overdiagnosis" and "overtreatment" are actively discussed over the past decade in many areas of contemporary medicine, including management of small thyroid nodules (3)(4)(5)(9)(10)(11). Avoiding overtreatment of patients with MPTCs became a challenging clinical problem in the field of endocrine oncology.…”
Section: Introductionmentioning
confidence: 99%
“…The notions of "overdiagnosis" and "overtreatment" are actively discussed over the past decade in many areas of contemporary medicine, including management of small thyroid nodules (3)(4)(5)(9)(10)(11). Avoiding overtreatment of patients with MPTCs became a challenging clinical problem in the field of endocrine oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in 2017, the United States Preventative Services Task Force issued a recommendation against screening for thyroid cancer in asymptomatic adults, giving the practice their lowest evidence rating of a D (indicating that the harms may outweigh the benefits), and more conservative staging and treatment guidelines have been recently established (18,19). Despite this, thyroid cancer overdiagnosis remains a persistent problem, with evidence that the majority of clinicians recommend tests that lead to overdiagnosis (20).…”
mentioning
confidence: 99%
“…A recent study indicated that more than 50% of physicians thought that total thyroidectomy for low-risk PTC was not overused, whereas more than 60% of physicians believed that radioiodine for low-risk PTC was overused (41). It implies that, regarding low-risk PTC treatment, conditional total thyroidectomy was acceptable and that radioiodine should be used less frequently.…”
Section: Discussionmentioning
confidence: 99%